EFFECTIVENESS OF SEMAGLUTIDE IN OBESITY TREATMENT AND THE ROLE OF LIFESTYLE INTERVENTIONS - Filip Bracichowicz; Igor Winogrodzki; Patryk Kowalczyk; Hanna Paszkiewicz; Kamil Nowak; Aleksandra Gęsińska; Alicja Stryczek-Schlusche; Bartłomiej Trzciński; Oliwia Gugała; Aleksandra Magdalena Furczyńska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Obesity is a global epidemic, affecting 13% of adults and driving type 2 diabetes, cardiovascular disease, and other comorbidities (World Health Organization, 2021). In Europe and the U.S., prevalence reaches 30–40%, with >20% in Poland (Gajewska & Harton, 2023). Lifestyle interventions alone often fail to ensure durable results, creating demand for adjunctive pharmacotherapy. Aim: To review obesity epidemiology and evaluate once-weekly semaglutide 2.4 mg regarding mechanism, efficacy, safety, and synergy with lifestyle changes. Materials and Methods: Narrative review of publications (2018–2025) from PubMed, Google Scholar, and other databases on obesity, GLP-1 analogs, and lifestyle trials. STEP program data, meta-analyses, and guidelines were included. Results: Risk factors include genetics, aging, sedentary lifestyle, and poor diet. Semaglutide, a GLP-1 receptor agonist, enhances insulin secretion, delays gastric emptying, and reduces appetite (Papakonstantinou et al., 2024). In STEP Phase 3 trials, semaglutide 2.4 mg weekly produced 15% mean weight loss over 68 weeks, versus 2–5% with placebo (Wilding et al., 2021) (Davies et al., 2021). About 69–79% achieved ≥10% loss, over half ≥15% (Davies et al., 2021). Safety was consistent with GLP-1 class, dominated by mild-to-moderate gastrointestinal events (Davies et al., 2021). Lifestyle modification alone yields 5–10% reduction, but in STEP 3, semaglutide plus intensive behavioral therapy achieved 16.0% versus 5.7% with lifestyle alone (Wadden et al., 2021). Continued lifestyle support is crucial to maintain outcomes and limit post-withdrawal regain. Conclusions: Semaglutide represents a breakthrough in obesity pharmacotherapy, approaching bariatric surgery efficacy in some patients. Optimal outcomes occur with integration of diet, activity, and education. Future dual/triple agonists may enhance efficacy, but issues of cost, access, and adherence persist. Broad, equitable availability is essential for public health.